UNDERSTANDING CRITICAL VARIABLE FOR CUSTOMER LOYALTY IN C2C MODE - Prasetya, Wibawa; Christine Natalia; Nesya Nathania Hanjaya; Dewi Kartikaningsih (Dinasti Publisher, 2022)
In twenty-first centuries, the development of e-commerce and market competition is aggravating. Traditional marketing pattern in society is undergoing profound changes and C2C e-commerce has become one of the most important shopping ways in our daily life. But due to the particularity of online shopping environment and various existing problems, it become more difficult to build customer loyalty. In terms of increasing customer loyalty, C2C must be able to provide customer trust from good service quality with promotion as a support. The purpose of this study is to determine the influence of service quality, promotion, and trust on customer loyalty from e-commerce customer. To clarify the relationship among these construct, SEM (Structural Equation Modeling) is conducted to examine the model fit and the five hypothesis. The result of this research shows that four of the five proposed hypotheses are accepted. Promotion has no significant influence on customer loyalty, but promotion will have a significant influence on customer loyalty through trust variable.